Utilization of Jatropha Leaf (Jatropa curcas) Extract as Immune System Enhancer of Vannamei Shrimp (Litopenaeus vannamei) Infected with Vibrio parahaemolyticus - Bagus Ansani Takwin; Dimas Putra Perdana; Muhaemi Muktiniati; Fariq Azhar (Department of Aquaculture, 2023)
The problem arises in vanamei shrimp cultivation is the emergence of diseases, such as vibriosis caused by Vibrio parahaemolyticus. Jatropha leaf extract can be used as an immunostimulant because it contains bioactive compounds namely flavonoid, tannins, saponins, and alkaloids. This research used a completely randomized design (CRD) with 5 treatments with 3 replications. The treatments used were; P1 (feed without extract and bacterial infection); P2 (feed without extract and NaCl injection); P3 : Feed + 1% + bacterial infection; P4 : Feed + 2% extract from feed and bacterial infection, P5 : Feed + 3% extract of feed and bacterial infection. Based on the results of the study, the administration of Jatropha leaf extract was able to increase the highest SR value of P2 by 88.3%, the highest THC value of P5 at 24.46 x 106 cells/ml, DHC values ​​such as hyaline cells ranged from 36.67-71%, granular cells ranged from 17-38.57%, and semigranular cells ranged from 12-24.67%, the highest AF value in P5 was 77.25%, and the lowest TBC value was at P2 of 6 x 108 CFU/ml, the lowest TVC value was at P2 of 0.56 x 106 CFU/ml. The higher the dose of extract given, the higher the THC and AF, besides that, Jatropha leaves were also able to increase the SR value and suppress the growth of total bacteria and total Vibrio in shrimp intestines.